2022
DOI: 10.1038/s41467-022-33991-6
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1-directed PlGF/VEGF blockade synergizes with chemotherapy by targeting CD141+ cancer-associated fibroblasts in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has a poor 5-year overall survival rate. Patients with PDAC display limited benefits after undergoing chemotherapy or immunotherapy modalities. Herein, we reveal that chemotherapy upregulates placental growth factor (PlGF), which directly activates cancer-associated fibroblasts (CAFs) to induce fibrosis-associated collagen deposition in PDAC. Patients with poor prognosis have high PIGF/VEGF expression and an increased number of PIGF/VEGF receptor-expressing CAFs, associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 76 publications
2
22
0
Order By: Relevance
“…Copyright 2021 Elsevier B.V.), (D) ECM (Reproduced with permission from Ref. 206 . Copyright 2022 Springer Nature), (E) exosomes or extracellular vesicles (Reproduced with permission from Ref.…”
Section: Future Pdtosmentioning
confidence: 99%
“…Copyright 2021 Elsevier B.V.), (D) ECM (Reproduced with permission from Ref. 206 . Copyright 2022 Springer Nature), (E) exosomes or extracellular vesicles (Reproduced with permission from Ref.…”
Section: Future Pdtosmentioning
confidence: 99%
“…At present, the use of effective vascular therapy for anti-tumor has been extensively studied. In the past clinical studies, the application of VEGF pathway inhibitors showed more effective anti-tumor effects, such as several inhibitors targeting VEGF pathway ( Ranieri et al, 2006 ; Costache et al, 2015 ; Kim et al, 2022 ), including bevacizumab and gemcitabine. In the experiment of pancreatic cancer in mice, blocking BICC1/LCN2 signal pathway can reduce the microvessel density and tumor volume of mouse PAAD cell grafts, enhance the antitumor effect of gemcitabine, and delay tumor growth ( Kooiman et al, 2020 ).…”
Section: Mechanism and Application Of Ultrasound Combined With Microb...mentioning
confidence: 99%
“…Chemotherapy resistance in PDAC is often associated with desmoplasia 93 , 94 , one of which was recently shown to occur through PlGF/VEGF-mediated activation of CAFs in an orthotopic PDAC mouse model treated with gemcitabine 95 . Therefore, the authors delicately designed and synthesized a multiparatopic VEGF decoy receptor (Ate-Grab), a fusion protein consisting of single-chain Fv of atezolizumab for targeting PD-L1-rich tumor tissues, fused to VEGF-Grab, which was previously developed to target PIGF/VEGF 96 , resulting in PD-L1-directed PlGF/VEGF blockade.…”
Section: Development Of Novel Therapeutic Strategies Against Tumor-pr...mentioning
confidence: 99%
“…Therefore, the authors delicately designed and synthesized a multiparatopic VEGF decoy receptor (Ate-Grab), a fusion protein consisting of single-chain Fv of atezolizumab for targeting PD-L1-rich tumor tissues, fused to VEGF-Grab, which was previously developed to target PIGF/VEGF 96 , resulting in PD-L1-directed PlGF/VEGF blockade. Indeed, Ate-Grab treatment relieved chemotherapy-induced desmoplasia in a PDAC model by sequestering PlGF/VEGF within the TME and thus inhibiting CAF activation, especially the CD141 + population, a key subset activated by gemcitabine treatment responsible for tumor fibrosis 95 .…”
Section: Development Of Novel Therapeutic Strategies Against Tumor-pr...mentioning
confidence: 99%